2019
DOI: 10.1186/s12884-019-2655-2
|View full text |Cite
|
Sign up to set email alerts
|

Continuous versus discontinuous suture in perineal injuries produced during delivery in primiparous women: a randomized controlled trial

Abstract: BackgroundThe technique used in the repair of a perineal injury resulting from childbirth could avoid discomfort and morbidity during the postpartum period. Recent studies show inconsistent results and support the need for new research with the inclusion of new health parameters not yet studied. Therefore, this study aims to evaluate if the suture technique (continuous or interrupted) has an effect on pain and other postpartum problems, incidence of incontinence (urinary and/or fecal), and the restart of sexua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…An earlier study by Hasanpoor et al [20] showed that pain severity was similar if repaired by either method. A recent study however showed that women who had a continuous suture repair had lower levels of pain [21]. These factors can be suggested to be taken into consideration in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…An earlier study by Hasanpoor et al [20] showed that pain severity was similar if repaired by either method. A recent study however showed that women who had a continuous suture repair had lower levels of pain [21]. These factors can be suggested to be taken into consideration in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, even in single-layer PJ, there are continuous and interrupted techniques, and no clinical controlled studies have been reported for these two suturing methods, while similar RCTs have been reported for the small intestine, mitral valve, and obstetric tract surgery. [18–20]…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, even in single-layer PJ, there are continuous and interrupted techniques, and no clinical controlled studies have been reported for these two suturing methods, while similar RCTs have been reported for the small intestine, mitral valve, and obstetric tract surgery. [18][19][20] This survey was also noteworthy with variations were also found in the suture material for PJ: 65% of cases undergoing double-layer PJ were given monofilament non-absorbable sutures for the outer layer, 35% were given absorbable sutures, and 55% and 41% were given 4/0 and 3/0 sutures, respectively. For inner layer anastomosis, the use of absorbable sutures, monofilament non-absorbable sutures, and 4/0 and 5/0 sutures were 60%, 37%, 45%, and 30%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…For the suture methods, it was reported that continuous suture can reduce the levels of pain, analgesia need and achieve better wound healing and shorter repair time, compared to discontinuous suture. 22,23 The wound healing after forceps delivery is affected by a variety of factors. Although the neonatal weight, the condition of amniotic fluid and times of vaginal checks were not included as a risk factor in our multivariate logistic regression analysis, they all showed significant differences in the univariate analysis, respectively, indicating that medical operators should also pay attention to these factors.…”
Section: Discussionmentioning
confidence: 99%